Sustainability in the financial sector in Kenya - Francis Kariuki (Kenya Bankers Association (KBA), 2015)
At the core of the concept of sustainability is the need to take into account the social, economic and environmental concerns in development. Sustainability ensures that economic growth takes into consideration social and environmental issues. In the financial sector, sustainability is necessary due to the critical role played by the sector in national development. In Kenya, financial institutions are financing investments in the agricultural, manufacturing, housing, infrastructural, energy and extractive industries. These investments have significant environmental and social impacts creating the need for adoption of sustainable finance. In spite of this, initiatives aimed at sustainability in the sector, are diverse and uncoordinated, and are therefore not likely to result in tangible long term benefits for society, environment and the business community. A synergistic approach to sustainability in the industry is thus imperative. The paper proposes the adoption of a hybrid approach in implementing sustainable banking in Kenya. The model would harness the positive attributes of market-driven and compliance approaches to regulation. Such a model could have voluntary codes and guidelines developed by the industry, and a regulator to enforce and ensure compliance with those guidelines.
Keywords: 330; Bank; Corporate Social Responsibility; Nachhaltige Kapitalanlage; Nachhaltige Entwicklung; Kenia